2016
DOI: 10.1111/trf.13815
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of severe postpartum anemia after Cesarean section

Abstract: Background Postpartum anemia is associated with maternal and perinatal morbidity. Population-level data may inform guideline development for postpartum anemia screening. Our objectives were to evaluate the associations between potential predictors (predelivery anemia and postpartum hemorrhage (PPH)) with severe postpartum anemia after cesarean section. Study Design and Methods Data were collected from 70,939 hospitalizations for cesarean section performed at Kaiser Permanente Northern California facilities b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
60
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 40 publications
8
60
0
3
Order By: Relevance
“…These findings are consistent with those by Butwick et al who reported that predelivery anemia is an independent risk factor for severe postpartum anemia after CD, classified by a postpartum Hb≤8 g/dl. 40 Furthermore, several obstetric societies, including The Royal College of Obstetricians and Gynecologists (UK) and the French College of Gynecologists and Obstetricians, have published PPH guidelines recommending that a Hb level above 8 g/dl is a therapeutic goal. 41 These observations, coupled with our findings, have important clinical relevance for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those by Butwick et al who reported that predelivery anemia is an independent risk factor for severe postpartum anemia after CD, classified by a postpartum Hb≤8 g/dl. 40 Furthermore, several obstetric societies, including The Royal College of Obstetricians and Gynecologists (UK) and the French College of Gynecologists and Obstetricians, have published PPH guidelines recommending that a Hb level above 8 g/dl is a therapeutic goal. 41 These observations, coupled with our findings, have important clinical relevance for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of seven observational studies, Hb levels were 0.51 g/dl lower in neonates born by CD compared with those born vaginally (Zhou et al, 2014). CD may reduce Hb and other haematolog- Additionally, delayed microbiota acquisition in children born by CD can affect their immunophysiological development and increase the risk of infections (Gronlund, Lehtonen, Eerola, & Kero, 1999), which would decrease iron absorption (Hurrell, 2012) may cause maternal anaemia (Butwick, Walsh, Kuzniewicz, Li, & Escobar, 2017) and reduce the amount of iron in breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…In their article, “Patterns and Predictors of Severe Postpartum Anemia after Cesarean Section,” Butwick and colleagues find that postpartum anemia is common, affecting 7.3% of the post‐Cesarean delivery population. As Cesarean delivery is the most frequently performed surgical procedure in the United States, with 1.3 million Cesarean deliveries in 2014, postpartum anemia after Cesarean delivery affects approximately 100,000 women annually .…”
mentioning
confidence: 99%
“…In the analysis by Butwick and colleagues, predelivery anemia was the most important predictor of postpartum anemia, accounting for 31% of cases . This observation suggests that a large proportion of cases of postpartum anemia may be preventable through better screening and treatment of predelivery anemia.…”
mentioning
confidence: 99%
See 1 more Smart Citation